2007
DOI: 10.1080/09540120701245999
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the HIV/AIDS Stigma Instrument—PLWA (HASI-P)

Abstract: This article describes the development and testing of a quantitative measure of HIV/AIDS stigma as experienced by people living with HIV/AIDS. This instrument is designed to measure perceived stigma, create a baseline from which to measure changes in stigma over time, and track potential progress towards reducing stigma. It was developed in three phases from 2003-2006: generating items based on results of focus group discussions; pilot testing and reducing the original list of items; and validating the instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
180
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(190 citation statements)
references
References 22 publications
7
180
1
2
Order By: Relevance
“…We started with a qualititative study based on focus group interviews to understand HIV stigma from the perspectives of nurses 1,2 and those living with HIV infection [3][4][5][6][7] and then developed two instruments to measure HIV stigma in the African context 4,8 . We then used these two instruments to monitor HIV stigma over the period of 1 year in all five countries, in a group of people living with HIV infection and a group of nurses.…”
Section: Introductionmentioning
confidence: 99%
“…We started with a qualititative study based on focus group interviews to understand HIV stigma from the perspectives of nurses 1,2 and those living with HIV infection [3][4][5][6][7] and then developed two instruments to measure HIV stigma in the African context 4,8 . We then used these two instruments to monitor HIV stigma over the period of 1 year in all five countries, in a group of people living with HIV infection and a group of nurses.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is of particular significance since the respondents are themselves nurses in the making and yet reveal strongly that bad attitudes of care providers prevent them from using available health care services It is vital to integrate peer education with reproductive health and HIV services to improve on the distribution of opportunities to access health services among young women (USAID & FHI 2006). Stigma hinders using of services such as voluntary counseling and testing (Holzemer et al 2007. In addition, 68% of the respondents indicated that women are shy in seeking health care services and that is a major barrier (Mba 2003).…”
Section: Discussionmentioning
confidence: 99%
“…§ Otros instrumentos que miden el mismo constructo: Algunos enunciados incluidos en otros instrumentos reconocidos que evalúan el mismo constructo fueron tomados como referencia para la redacción de algunos de los ítems preliminares. Los instrumentos considerados fueron: HIV Stigma Scale (Sowell et al, 1997), HIV Stigma Scale (Berger et al, 2001), HIV/AIDS Stigma Instrument -PLWA (HASI-P, Holzemer et al, 2007), Internalized Stigma Scale , HIV Related Stigma Scales (Visser et al, 2008), HIV/AIDS Stigma Scale para Latinos GBT (Molina & Ramirez-Valles, 2013) y Van Rie HIV/AIDS-Related Stigma Scale (Kipp et al, 2015). Particularmente, se consideraron aquellos ítems que funcionaban psicométricamente bien en sus instrumentos de origen, que eran teóricamente muy representativos de la dimensión a la que correspondían y/o describían situaciones que habían sido mencionadas por las personas entrevistadas como habituales en el contexto del AMBA.…”
Section: B Preparación De Los Reactivosunclassified